Association between ultrasound assessment of glenohumeral subluxation and shoulder pain, muscle strength, active range of movement and upper limb function in people with stroke. (3rd March 2020) - Kumar, Praveen; Bradley, Michael; Gray, Selena; Swinkels, Annette
Abstract: Background: Glenohumeral subluxation (GHS) is a commonly reported post-stroke complication which has a negative effect on rehabilitation. Objective: To explore the association between GHS and other clinical outcomes in people with post-stroke hemiplegia. Methods: Patients with post-stroke hemiplegia ( n  = 105, 71 ± 11 years, median time since stroke 5.6 weeks), who gave informed consent, were recruited. GHS was assessed by the ultrasound method. Assessment of shoulder pain (visual analogue scale), active range of movement (AROM), muscle strength (Medical Research Council Scale), muscle tone (Modified Ashworth Scale) and the upper limb section of the Motor Assessment Scale (MAS) was undertaken. Results: GHS was present in 65 (62%) patients. There was a moderate negative correlation between GHS and muscle strength ( r = −0.54, p  < .01); MAS score ( r = −0.58, p  < .01); flexion ( r = −0.54, p  < .01), abduction ( r = −0.53, p  < .01), and external rotation ( r = −0.52, p  < .01) but not between GHS and muscle tone ( r = −0.18, p  > .05) and pain ( r  = 0.06, p  > .05). Stepwise linear regression analysis showed that muscle strength, external rotation of the shoulder and GHS were associated with upper limb function (adjusted R 2 =0.83, p  < .01). Conclusion: The relationship between GHS, shoulder AROM, muscle strength and upper limb function suggests that patients with GHS are more like to have a poor motor recovery.